The peripheral focus on the psychological parameters of parents of autistic children in the intervention methods: A review and recommending the strategy, focusing psychological parameters of parents of autistic children in intervention methods - Vidya, Bhagat; Nordin, Simbak; Mainul, Haque (2015)
The experience of parents with an Autism Spectrum Disorders (ASD) can be devastating. Parents and families have to cope with the compound, demanding situation in their life. The presence of pervasive and severe deficits in children with ASD increases the adjusting demands of parent’s in their life situations. Those coping with life complexity with the parents of ASD nudge them into stress later into distress slowly incapacitates them that of their efficiency to deal with this situation. These parents are found with disturbances in their psychological parameters such as social, sexual, economic, and emotional. Perhaps this shatters them from their interpersonal relationship and family life. Indeed, these aspects of parental distress stand lower in position, and the focus goes with the treatment of ASD. Thus, the management of ASD by these parents to their deficit child capacitating to reach their fullest abilities remains questionable. Thus, there is a need for intervention of autistic children with a peripheral focus on psychological parameters of parents of ASD. This review study focuses on division of attention required for the treatment of ASD towards the child with autism and the parents who manage them.